Personal Branding Vegan Influencer di Instagram - Viendra Salsabila Harahap; Hanny Hafiar; Diah Fatma Sjoraida (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
Indonesia is the 16th best country to live a vegan lifestyle. Even so, the number of vegans in Indonesia is still small. The purpose of this research is to find out the meaning of vegan for vegan influencers, the motives of vegan influencers in building personal branding on Instagram, and vegan influencer communication experiences in building personal branding on Instgaram. The theory used in this research is Schutz's Phenomenology Theory and Symbolic Interaction Theory by George Herbert Mead. This research uses the phenomenological method and constructivism paradigm. The results of this study from 10 subjects, indicate that vegan influencers define vegan as and for health, environment, ethics, and food. The vegan influencer motives are categorized into 2 categories, firstly because-motive and in-order-to-motives. Vegan influencer communication experiences in building personal branding on Instagram are divided into two, namely the communication experience when you first became a vegan influencer on Instagram and after becoming a vegan influencer on Instagram. The advice that can be given from this research is that vegan influencers are expected to be more consistent in creating content, increase content about simple vegans, better understand and frequently use Instagram features, and for further research it is hoped that it can develop research on vegan influencers in the influencer marketing aspect.